2023
DOI: 10.3390/vetsci10010042
|View full text |Cite
|
Sign up to set email alerts
|

Human ELISA Detects anti-SARS-CoV-2 Antibodies in Cats: Seroprevalence and Risk Factors for Virus Spread in Domestic and Stray Cats in Bulgaria

Abstract: The aim of this study was to verify whether the human DR-ELISA for the detection of anti-SARS-CoV-2 antibodies can be applied in cats, and to assess the risk factors that determine the spread of the virus among the cat population in Bulgaria. The study included 92 serum samples collected from 68 domestic and 24 stray cats aged from 3 months to 20 years of age in the period of January–June 2021. The samples originated from three regions in Bulgaria and from three places of inhabitance. DR-ELISA based on peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Dogs lead the chart at 33%, followed by cats at 29% [5]. Since both domestic animal species not only proved to be susceptible to infection with SARS-CoV-2 in early animal trials [6][7][8][9] but also showed a regular occurrence of natural infections in various prevalence studies around the world [10][11][12][13][14][15][16][17][18][19][20][21][22][23], the question arose of what the consequences of an infection with SARS-CoV-2 are not only for the animals themselves but also for the households and in a broader context, the direct environment of the infected animal.…”
Section: Introductionmentioning
confidence: 99%
“…Dogs lead the chart at 33%, followed by cats at 29% [5]. Since both domestic animal species not only proved to be susceptible to infection with SARS-CoV-2 in early animal trials [6][7][8][9] but also showed a regular occurrence of natural infections in various prevalence studies around the world [10][11][12][13][14][15][16][17][18][19][20][21][22][23], the question arose of what the consequences of an infection with SARS-CoV-2 are not only for the animals themselves but also for the households and in a broader context, the direct environment of the infected animal.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence for the spread of SARS-CoV-2 among cats in Bulgaria, and domestic cats with outdoor access play an important role in this. 32 We speculate that, when such cats traveled with their owners from the capital city to the countryside, e.g. to the Sandanski Municipality (particularly before or during lockdown), they might have contributed to the virus spread to some extent, [57][58][59] with possible transmission human↔cat→cat→human.…”
Section: Discussionmentioning
confidence: 97%
“…20,21 An important part of controlling the spread of respiratory viruses is the availability of reliable diagnostic assays. The serological diagnosis of SARS-CoV-2 utilizes assays with different characteristics (antibody types and quantity), based on various principles, such as quick antigen tests based on nanoparticles, 29,30 qualitative and quantitative ELISA, immunofluorescence, [31][32][33] electrochemiluminescence assay 34 and automated systems. 35,36 Different serological tests also have different informativeness depending on the team and the combination of antibodies they prove.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study validated and applied nested (n) One-Step RT PCR for SARS-CoV-2 detection in swab samples [ 51 ] and sera from cats [ 52 ]. The assay showed high sensitivity, as it was able to detect low concentrations of virus RNA.…”
Section: Introductionmentioning
confidence: 99%